Age and practice effects on inter-manual performance asymmetry - Francis, Karen L.; MacRae, Priscilla G.; Spirduso, Waneen W.; Eakin, Tim (Frontiers in Psychology, 2015)
Manual dexterity declines with increasing age however, the way in which inter-manual asymmetry responds to aging is unclear. Our purpose was to determine the effect of age and practice on inter-manual performance asymmetry in an isometric force pinch line tracing task that varied in difficulty within segments. Thirty right handed participants, 5 males and 5 females in each of three age groups, young (Y20), young-old (O70), and old-old (O80), practiced an isometric force pinch task for 10 trials with each hand on each of five consecutive days. Inter-manual performance asymmetry of the right and left hands was analyzed with a repeated measures ANOVA of asymmetry with age groups, practice, task difficulty, and hand as factors. The within-individual magnitude of asymmetry was also analyzed with a repeated measures ANOVA of manual asymmetry calculated as an asymmetry index (AI). Post hoc pair-wise comparisons were performed when significance was found. We observed no inter-manual performance asymmetry on this isometric tracing task among any of the age groups, either in the hand performance differences or in the magnitude of the asymmetry index (AI). Age and practice interacted in terms of manual performance: the Y20 and O70 group improved accuracy and task time across the five days of practice but the O80 group did not. However, practice did not differentially affect the AI for accuracy or task time for any group. Accuracy of performance of the two hands was differentially affected by practice. All age groups exhibited poorer performance and larger AIs on the most difficult segments of the task (3 and 6) and this did not change with practice.